2011
DOI: 10.1002/cncr.26305
|View full text |Cite
|
Sign up to set email alerts
|

Axillary lymph node failure in patients treated with accelerated partial breast irradiation

Abstract: BACKGROUND: Data on the risk of axillary failure (AF) after accelerated partial breast irradiation (APBI) are limited. In this study, the authors determined the rate of AF and regional lymph node failure (RNF) in patients who received various forms of APBI and identified factors that were associated with its occurrence. METHODS: In total, 534 patients with early stage breast cancer were treated at William Beaumont Hospital with APBI, including 466 patients (87%) with invasive breast cancer and 68 patients (13%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…A registry trial of 1,500 patients treated with the MammoSite device has reported LR in 3.8% and AF in 0.79% with mean follow‐up of 5 years, the rate of LR and AF after MammoSite APBI is low and appears to be similar to that achieved with WBI . Another trial of 534 patients treated with three APBI techniques included interstitial brachytherapy ( n = 221), balloon‐based brachytherapy ( n = 207), and 3D‐CRT ( n = 106) has also reported a low AF (0.19%) with follow‐up of 5 years . The results of these trials are consistent with our analysis.…”
Section: Discussionmentioning
confidence: 98%
“…A registry trial of 1,500 patients treated with the MammoSite device has reported LR in 3.8% and AF in 0.79% with mean follow‐up of 5 years, the rate of LR and AF after MammoSite APBI is low and appears to be similar to that achieved with WBI . Another trial of 534 patients treated with three APBI techniques included interstitial brachytherapy ( n = 221), balloon‐based brachytherapy ( n = 207), and 3D‐CRT ( n = 106) has also reported a low AF (0.19%) with follow‐up of 5 years . The results of these trials are consistent with our analysis.…”
Section: Discussionmentioning
confidence: 98%